Reconstructing Past Seasonal to Multicentennial‐Scale Variability in the NE Atlantic Ocean Using the Long‐Lived Marine Bivalve Mollusk Glycymeris glycymeris. (9th November 2017) - Reynolds, D. J.; Hall, I. R.; Slater, S. M.; Scourse, J. D.; Halloran, P. R.; Sayer, M. D. J.
Abstract: The lack of long‐term, highly resolved (annual to subannual) and absolutely dated baseline records of marine variability extending beyond the instrumental period (last ~50–100 years) hinders our ability to develop a comprehensive understanding of the role the ocean plays in the climate system. Specifically, without such records, it remains difficult to fully quantify the range of natural climate variability mediated by the ocean and to robustly attribute recent changes to anthropogenic or natural drivers. Here we present a 211 year (1799–2010 C.E.; all dates hereafter are Common Era) seawater temperature (SWT) reconstruction from the northeast Atlantic Ocean derived from absolutely dated, annually resolved, oxygen isotope ratios recorded in the shell carbonate (δ 18 Oshell ) of the long‐lived marine bivalve mollusk Glycymeris glycymeris . The annual record was calibrated using subannually resolved δ 18 Oshell values drilled from multiple shells covering the instrumental period. Calibration verification statistics and spatial correlation analyses indicate that the δ 18 Oshell record contains significant skill at reconstructing Northeast Atlantic Ocean mean summer SWT variability associated with changes in subpolar gyre dynamics and the North Atlantic Current. Reconciling differences between the δ 18 Oshell data and corresponding growth increment width chronology demonstrates that 68% of the variability in G . glycymeris shell growth can be explained by the combined influence of biological productivity and SWT variability. These data suggest that G . glycymeris can provide seasonal to multicentennial absolutely dated baseline records of past marine variability that will lead to the development of a quantitative understanding of the role the marine environment plays in the global climate system. Key Points: The application of δ 18 O data derived from Glycymeris glycymeris shells is evaluated as a new robust paleoceanographic proxy Subannual and annually resolved δ 18 O data demonstrate significant skill at reconstructing NE Atlantic seawater temperature variability The δ 18 Oshell record is sensitive to North Atlantic variability linked to changes in subpolar gyre dynamics and the North Atlantic Current